2021
DOI: 10.1177/21526567211003844
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Control of Chronic Rhinosinusitis With Nasal Polyps: A Comparison in Patients With or Without NERD

Abstract: Objectives The aim was to compare the control of chronic rhinosinusitis with nasal polyps (CRSwNP) after endoscopic sinus surgery (ESS), in patients with/without nonsteroidal anti-inflammatory drug exacerbated respiratory disease (NERD). Study Desing: A retrospective hospital-based sample of CRSwNP patients with/without NERD with follow-up. Setting Tertiary rhinology centers. Methods Electronic patient record data from 116 CRSwNP patients (46 with NERD and 70 without NERD) undergoing ESS during 2001–17 were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 41 publications
2
24
0
Order By: Relevance
“…The current study showed that CRSwNP, asthma, and NERD are important predictors of revision ESS also at the individual level. In accordance to this, previous studies have demonstrated on hospital population level that several factors are associated with the CRS recurrence and/or revision ESS, such as CRSwNP, asthma, AR, NERD, eosinophilia and smoking 1,7,23,24 . CRSwNP patients with co-morbid asthma and/or NERD have an increased risk for recurrence and revision ESS, although these patients seem benefit from initial ESS 13,19,[25][26][27] .…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The current study showed that CRSwNP, asthma, and NERD are important predictors of revision ESS also at the individual level. In accordance to this, previous studies have demonstrated on hospital population level that several factors are associated with the CRS recurrence and/or revision ESS, such as CRSwNP, asthma, AR, NERD, eosinophilia and smoking 1,7,23,24 . CRSwNP patients with co-morbid asthma and/or NERD have an increased risk for recurrence and revision ESS, although these patients seem benefit from initial ESS 13,19,[25][26][27] .…”
Section: Discussionsupporting
confidence: 76%
“…CRSwNP patients with co-morbid asthma and/or NERD have an increased risk for recurrence and revision ESS, although these patients seem benefit from initial ESS 13,19,[25][26][27] . This may reflect a more severe disease, with usually co-morbid NERD, anosmia, Type 2 high eosinophilic inflammation, and a greater tendency of polyp re-growth 23,[28][29][30][31][32][33][34][35][36][37] . When performing SFS, Immunodeficiency or its suspicion showed also to one of the top ten predictors by all three classifiers.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that CRSwNP, asthma and NERD represent important predictors of revision ESS at the individual level. In accordance with this, previous studies demonstrated at the hospital population level that several factors associate with CRS recurrence and/or revision ESS, including CRSwNP, asthma, allergic rhinitis, NERD, eosinophilia and smoking [1,13,57,58]. CRSwNP patients with a comorbidity of asthma and/or NERD carry an increased risk for recurrence and revision ESS, although these patients appear to benefit from an initial ESS [19,41,[59][60][61].…”
Section: Plos Onesupporting
confidence: 71%
“…Furthermore, data were lacking for some other important factors, such as postoperative treatment, validated symptoms, endoscopic nasal polyp score, medication, the Lund Mackay score for sinus computed tomography scans, smoking status, eosinophils and the extent of baseline ESS. Yet, some of these variables, such as smoking [13] or total ethmoidectomy, have not emerged as strong predictors of revision ESS compared with Type 2 high diseases [57] in our previous studies. That said, we acknowledge that the inclusion of more variables and additional cases would most likely improve our estimates.…”
Section: Plos Onementioning
confidence: 57%
See 1 more Smart Citation